BEANS PEDDLERS IN ALEXANDRIA CITY STREETS, FIELD WORK STUDY IN CULTURAL AND BEHAVIORAL GEOGRAPHY - Mohamed Nour Eldin El-Sabawy (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
During his career in the streets of Alexandria, especially in the morning and afternoon, the researcher noted that a lot of people are crowded around a weak wooden car made of a special form that allows a lot of bottles of oil and salty things and vinegar and quantities of appearances and other things on the shelves, and inside this big bottles of beans, which spreads in Alexandria city from Al.'Agamy suburb in the west to Abo Qir in the east. The research deals with a field study of the Beans Peddlers in Alexandria city streets through a number of topics including: Research Introduction, Research Background, Paper aims. This paper aims at studying some observations, procedures of study, study tools, home site, and migration causes.